Reaching Syrian migrants through Dutch municipal registries for hepatitis B and C point-of-care testing - Chrissy P. B. Moonen; Elfi E. H. G. Brouwers; Christian J. P. A. Hoebe; Nicole H. T. M. Dukers-Muijrers; Jamila Bouchaara; Inge H. M. van Loo; Casper D. J. den Heijer (PLoS ONE, 2025)
Undetected chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infections can lead to cirrhosis and liver cancer. Syrian migrants are the largest non-European migrant group in the Netherlands with HBV and HCV prevalence rates above 2%. This study aimed to reach Syrian migrants for HBV and HCV testing using point-of-care tests (POCT). A multifaceted strategy was employed to reach Syrian migrants aged ≥16 years from two Dutch municipalities for free-of-charge HBsAg and anti-HCV POCT using finger prick blood at the regional Public Health Service. All were personally invited by the Public Health Service by postal mail, based on municipal registry data. Respondents’ medical history data were analysed descriptively and data on age, sex, and municipality were compared with non-participating invitees, using Pearson’s Chi-square test. Of the study population (N = 832), 32.3% (n = 269) attended the testing. The mean age of participants was 36 years (range 16–70), 59.1% were men, and 66.5% were unemployed. Non-participation was higher in the younger age groups (<30 years) (p < .001). The POCT using finger prick blood was well received. None tested HBsAg or anti-HCV positive. With approximately one-third of participation, this study demonstrated relatively high reach of Syrian migrants for testing, compared to studies with similar recruitment methods. However, while the reach could be considered successful, testing failed to demonstrate new infection in this key population. Thereby, other methods may be preferred to identify new HBV and HCV infections, such as opportunistic testing within existing care processes.